Antimicrobial photodynamic therapy: study of bacterial recovery viability and potential development of resistance after treatment - Tavares, Anabela (2020)
Antimicrobial photodynamic therapy (aPDT) has emerged in the clinical field as a potential alternative to antibiotics to treat microbial infections. No cases of microbial viability recovery or any resistance mechanisms against it are yet known. 5,10,15-tris(1-Methylpyridinium-4-yl)-20-(pentafluorophenyl)-porphyrin triiodide (Tri-Py(+)-Me-PF) was used as photosensitizer. Vibrio fischeri and recombinant Escherichia coli were the studied bacteria. To determine the bacterial recovery after treatment, Tri-Py(+)-Me-PF (5.0 microM) was added to bacterial suspensions and the samples were irradiated with white light (40 W m(-2)) for 270 minutes. Then, the samples were protected from light, aliquots collected at different intervals and the bioluminescence measured. To assess the development of resistance after treatment, bacterial suspensions were exposed to white light (25 minutes), in presence of 5.0 microM of Tri-Py(+)-Me-PF (99.99% of inactivation) and plated. After the first irradiation period, surviving colonies were collected from the plate and resuspended in PBS. Then, an identical protocol was used and repeated ten times for each bacterium. The results suggest that aPDT using Tri-Py(+)-Me-PF represents a promising approach to efficiently destroy bacteria since after a single treatment these microorganisms do not recover their viability and after ten generations of partially photosensitized cells neither of the bacteria develop resistance to the photodynamic process.